The Seattle puzzle - Warner, Gertrude Chandler, 1890-1979.; Papp, Robert (Morton Grove, Ill. : A. Whitman & Co., 2007)
When the Alden children accompany their grandfather on a trip to Seattle, they discover clues throughout the city, seemingly planted just for them.
Keywords: Boxcar children (Fictitious characters) -- Juvenile fiction; Orphans -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Seattle (Wash.) -- Juvenile fiction; Mystery fiction